The Validity Of Notary's Testamentary Grant Deed To Adopted Children In The Perspective Of Islamic Inheritance Law - Dedi; Syhabudin, Abu; Ropiah, Siti; Syafi'i; A. Nururrochman Hidayatulloh (Faculty of Law, Universitas Pekalongan, 2025)
In Indonesian legal practice, the granting of assets to adopted children through testamentary grants often causes debate due to differences in views between Islamic law and civil law. Adopted children are not considered as heirs in the perspective of sharia, but positive law allows such granting through a testamentary grant deed made by a notary. This study is conducted with a normative legal research method using statutory and conceptual approaches. The aim is to understand the extent to which a deed of testamentary grant to an adopted child can be considered valid under national law as well as in accordance with sharia principles. The results of the analysis show that the testamentary grant deed made by a notary is formally valid according to the Civil Code and the Notary Office Law because it fulfills the elements of an authentic deed and has perfect evidentiary power. However, in the Islamic inheritance law system formulated in the Compilation of Islamic Law (KHI), gifts to adopted children are limited through the mechanism of compulsory testament, which is a maximum of only one third of the inheritance and must not harm the absolute rights of legal heirs. If the gift exceeds this limit or is made without the consent of the heirs, the religious court has the authority to cancel the deed. This disharmony creates a conflict of norms that results in legal uncertainty. Therefore, normative integration is needed to ensure that the testamentary grant deed is legally, socially and shar'i acceptable.